Kapasistas Organisasi Lokal dalam Sertifikasi Hutan di Kabupaten Gunungkidul - SULISTYANINGSIH, SULISTYANINGSIH (Jurnal Studi Pemerintahan, 2010)
The existence of people forest in Java was marginalized for a long time has changed. It was happened after state deforestation in Java. It can be shown by people forest in Gunung Kidul District,Yogyakarta. The people forest has gotten sertification strenghten the legitimation of real people role in forest management. In this context is needed local institution strenghten. The strong local institution is hoped to become social capital for community in people forest management . It makes farmers of people forest have strong and high bargaining posistion toward market intervention. But, in this case, state role in market intervention become important factor too. State must give protection toward the farmers of people forest.